Insidious : chapter 3 - Whannell, Leigh, 1977-; Mulroney, Dermot; Scott, Stefanie, 1996-; Shaye, Lin, 1943- (Culver City, California : Sony Pictures Home Entertainment, 2015)
After a teenager becomes the target of an evil supernatural entity, Elise Rainier agrees to help her get rid of the demon.
Originally released as a motion picture in 2015.
Sequel to the film "Insidious : chapter 2" (2013).
Dolby digital surround, anamorphic wide screen 1.85:1.
Features: digital copy of the film.
Dermot Mulroney, Stefanie Scott, Lin Shaye, Leigh Whannell, Angus Sampson.
MPAA rating: PG-13.
Keywords: Demoniac possession -- Drama; Supernatural -- Drama; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films; Horror films